PENGEMBANGAN ASET TERITORIAL SEBAGAI BASIS PERENCANAAN PEMBANGUNAN - Ahyuni ahyuni (JURNAL GEOGRAFI, 2013)
Abstrak Assets-based development is a theoritical approach have been developed for development planning for more optimistic, relying on endegenous development, more innovative and have ability to enhance the capacity and mobilize assets to transform the society. This approach criticized needs-oriented solution in development thinking that is development driven by external resources and more emphasized mapping problem and deficiency on people and place. As consequences, pessimism is growing and so many resources or assets existed or potential in a territory is neglected. This article discussed concept of assets-based planning and compared it with needs-oriented approach. Some examples from Indonesian development planning cases are also described.